2020
DOI: 10.1111/ene.14566
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy, functional outcome and treatment effect of intravenous alteplase for acute ischaemic stroke

Abstract: Background and purposePolypharmacy is an important challenge in clinical practice. Our aim was to determine the effect of polypharmacy on functional outcome and treatment effect of alteplase in acute ischaemic stroke.MethodsThis was a post hoc analysis of the randomized, placebo‐controlled WAKE‐UP trial of magnetic resonance imaging guided intravenous alteplase in unknown onset stroke. Polypharmacy was defined as an intake of five or more medications at baseline. Comorbidities were assessed by the Charlson Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Our results confirmed a high prevalence of polypharmacy in stroke patients with up to 45% of our patients taking 5 or more medications [16,17,19]. Polypharmacy in stroke patients have been reported to be associated with poor functional outcome [15]. In accordance to that, poor functional outcome was also more common in our patients with polypharmacy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results confirmed a high prevalence of polypharmacy in stroke patients with up to 45% of our patients taking 5 or more medications [16,17,19]. Polypharmacy in stroke patients have been reported to be associated with poor functional outcome [15]. In accordance to that, poor functional outcome was also more common in our patients with polypharmacy.…”
Section: Discussionsupporting
confidence: 90%
“…The highest level of prescribing is observed in patients with cardiovascular risk factors [13], especially diabetes and coronary heart disease [14]. In stroke patients polypharmacy is associated with worse functional outcome [15]. Furthermore, the intake of a higher number of drugs is associated with lower possibility of discharge home [16], with the severity of poststroke fatigue [17], progression of cognitive impairment [18], and increased number of falls [19].…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy was present in 31.5% of our patients, which is in the upper range of reported polypharmacy rates between 10 and 30% in previous studies ( 28 , 31 33 ). While in univariate analysis, polypharmacy had a negative association with both outcome measures, this association was no longer present in multivariate analysis.…”
Section: Discussionsupporting
confidence: 59%
“…A high comorbidity burden in patients with AIS is a growing challenge in clinical practice and patient management. Previous studies reported 19% to 64% of stroke patients presenting with a CCI Score ≥2 ( 27 , 28 ). In an aging society, the comorbidity burden of patients is likely to increase further.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation